ANALISIS KINERJA SIMPANG TIRTO AGUNG DAN SIMPANG JALUR MASUK KELUAR TOL SEKSI B SEMARANG - Adhetea Anggun Gitario Ajitama; Ari Setiawan; Djoko Purwanto; Rudi Yuniarto Adi (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Tirto Agung Intersections and the ramp Intersection of Section B Semarang Toll, they located in Prof. Soedarto, SH Street. The third intersection is an unsignalized intersection and has high traffic volume because it is one's access to education and a fairly dense residential area. Other that there is u-turn between ramp intersection Toll Road Semarang Section B dan Tirto Agung intersection that densely. With the problem affects the performance of the fall in traffic intersections. The purpose of this study was to analyze the performance and determine the pattern of traffic movements at each intersection. Primary data were collected by direct observation and survey on all three intersections. The observed data are geometric intersection, intersection volume, vehicle speed, long queues of vehicles, number of vehicles turning, turning vehicle duration, the identification of origin purpose from vehicle. The data obtained are used to analyze the performance of the intersection on the analysis of existing conditions and vehicle turning direction. The method of calculating the performance of intersections refer to Indonesia Jalan Capacity Manual 1997. The research results which are shown the greatest degree of saturation is the entrance intersection of Section B Semarang Toll with the analysis results 0,92 on existing condition. The degree of saturation can be falsified into 0,74 with a median implement an alternative solution extends the reach of Section B pathway Semarang Toll Road and broadening Prof. Soedarto, SH being 15.80 meters. But this solution only lasted two years only, so it becomes less meaningful.